KESESUAIAN PEMANFAATAN RUANG MENINJAU PROGRAM STRUKTUR RUANG DAN POLA RUANG KABUPATEN PRINGSEWU TAHUN 2017-2021 - Aswad, Fatmawati Hajar; Affandi, Muhammad Irfan; Mayaguezz, Henky (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2024)
This study aims to analyze the suitability of the use of programs and activities in the spatial structure and spatial pattern of Pringsewu Regency for 2017-2021. In this study using the Scoring and Weighting Methods to determine the suitability and quality values of spatial use in terms of spatial structure and spatial patterns in Pringsewu Regency in 2017-2021, after obtaining the weighting percentage, it can be put into GIS analysis. So the results of the study show that the suitability of spatial use in 2017-2019 and 2020-2021 has an increase in the suitability of spatial use up to 8.07% with an average weight percentage of 37.34%, namely spatial planning is not in accordance with spatial planning and affects the quality of spatial planning. The incompatibility of spatial planning with the Pringsewu District Spatial Planning is due to the influence of local government policies, investors and the community within it. The consistent use of space is implemented in Sukoharjo District, Gadingrejo District, Pagelaran District, Pringsewu District, and Ambarawa. So that policies are needed that are in line between the government and regional spatial planning so that they are sustainable and able to improve the quality of sustainable spatial planning in Pringsewu Regency as one of the areas planned to become a fast-growing area in Lampung Province.